Current status on the use of recycled aggregates in concrete: Where do we go from here? - Jorge de Brito (RILEM Technical Letters, 2016)
The consumption of energy and natural resources has been growing exponentially with the significant increase of the economic and industrial activities of the semi-developed nations, becoming one of the major environmental concerns in our time. Several sectors are already pursuing cost-effective solutions to the problem of dumping waste, by reducing their production and adding value to them through their reuse or recycling them into new products, in view of a circular economy. Here, the current state of the recycled aggregates’ application in the concrete industry is briefly reviewed, with a particular focus on the existing obstacles to their widespread use and lacking knowledge in general areas, which need to be further researched.